2017
DOI: 10.11138/ads/2017.8.3.110
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge and attitude among caregivers of special needs patients at a Comprehensive Rehabilitation Centre: An Analytical Study

Abstract: Caregivers showed a deficiency in the proper oral health attitude. To improve oral health attitudes of caregivers, dental education plus training programs should be given high priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…Two things remain unclear however: i) the length of time the effects of the educational interventions last; and ii) how unpaid family caregivers could access these educational opportunities. The first issue is vital; just because caregivers know how to clean teeth, does not mean that they know the value of oral hygiene [27]. Staff motivation to provide support that is enabling and of high quality differs depending on organisational culture [74, 75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two things remain unclear however: i) the length of time the effects of the educational interventions last; and ii) how unpaid family caregivers could access these educational opportunities. The first issue is vital; just because caregivers know how to clean teeth, does not mean that they know the value of oral hygiene [27]. Staff motivation to provide support that is enabling and of high quality differs depending on organisational culture [74, 75].…”
Section: Discussionmentioning
confidence: 99%
“…Studies also revealed that lower caregiver education was associated with greater caregiver burden and less preventative dental care use [26]. Caregivers’ attitude towards oral health of special needs patients was found relatively unsatisfactory even though their knowledge was adequate [27]. If interventions to improve the oral health of people with IDD are to be implemented effectively, barriers faced by caregivers should be identified and carefully considered in the investigation and evaluation of these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Since SCPs highly dependent on their caregivers’ perception toward oral health, this could be the reason of the lack of SCPs in dental practice encountered by the participants in this study. It is documented that caregivers of SCP understood that oral care was important, however, there were still some who thought that it was not essential and dental visits should only be performed when the patients were in pain [ 40 ]. Preventive measure for this cohort will always require the cooperation, positive attitude, and continued interest and treatment priorities of the caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…We also speculate that with appropriate training, the spatula may aid toothbrushing by caregivers, who also have difficulty accessing the oral cavity of people with disability and thus struggle to provide adequate preventive oral care [ 43 45 ]. Studies on this issue are pending.…”
Section: Discussionmentioning
confidence: 99%